What Drives Non Performing Financing? Evidence from Islamic Rural Banks in Indonesia During Covid-19 - Kadir, Rifadli D; Ratnasari, Sri Langgeng; Abduh, Muhamad Abduh (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to investigate the factors that influence non-performing financing (NPF) at Islamic rural banks (BPR) in Indonesia during the Covid-19 pandemic. The data used in this study was taken during the COVID-19 pandemic, namely in 2020. This study uses a data panel consisting of 128 Sharia BPRs throughout Indonesia. The analysis used is panel data analysis by choosing the best model between common effect (CE), fixed effect (FE), and random effect (FE). Data analysis was also carried out on: (1) large and small Sharia BPRs; (2) BPR located on the island of Java and outside the island of Java. The results found that the variable that had a strong influence on NPF during the covid-19 pandemic was economic growth as proxied by Gross Regional Domestic Product (GRDP). Bank size shows a negative and significant effect. FDR shows a positive and significant effect. Operational efficiency ratio (OER/BOPO) has a positive but not significant effect. Based on these results, it is necessary to mitigate financial problems, especially changes in macroeconomic conditions such as economic growth. This study also shows that there are differences in the variables that affect the size of small and large banks, as well as those in Java and those outside Java. This result can be a reference for Sharia BPR in mitigating financing risk.